O multiverso predatório dos deuses canibais: o legado de Joanna Overing - Els Lagrou; Luisa Elvira Belaunde (Journal de la Société des Américanistes)
In this article we explore Joanna Overing’s contributions to the ethnology of the South American Lowlands, in dialogue with the main theoretical issues addressed by the subdiscipline. In this sense, we propose a brief intellectual biography of an American anthropologist born in 1938 who did fieldwork in Venezuela, taught in the United States, England and Scotland, weaved interdisciplinary dialogues between philosophy, linguistics and anthropology and stimulated exchanges between ethnology carried out in England, France, Scandinavia and Brazil. As the only woman in the anthropology department at the London School of Economics for much of the eighties, she faced pioneering controversies about kinship, gender, rationality, temporality, aesthetics and creativity with elegant, clear and theoretically dense writing, making room for women in academia. Both in London and in Saint Andrews she marked her presence, had many students and with them set key guidelines for future developments in anthropology.